Construction of hierarchical nickel cobalt selenide complex hollow spheres for pseudocapacitors with enhanced performance. (10th August 2018) - Quan, Liang; Liu, Tianqing; Yi, Mingjie; Chen, Qidi; Cai, Daoping; Zhan, Hongbing
Abstract: Construction bimetallic transition metal selenides with complex hollow structures is of significant importance but also extremely challenging. In this work, starting form metal-organic frameworks (MOFs), we have successfully synthesized the unique hierarchical (Ni0.33 Co0.67 )Se2 complex hollow spheres (CHSs), which manifest high specific capacitance as well as excellent rate performance and cycling stability, making them promising electrode materials for pseudocapacitors. The hierarchical (Ni0.33 Co0.67 )Se2 CHSs display a high specific capacitance of 827.9 F g −1 at the current density of 1 A g −1 and can still retain 646.2 F g −1 at a very high current density of 30 A g −1 . Besides, a high capacitance of 865.8 F g −1 is obtained after cycling at 6 A g −1 for 2000 cycles, indicating good cycling stability. The excellent electrochemical performance could be owing to their high electrical conductivity and hierarchical complex hollow structure. Furthermore, an asymmetric supercapacitor (ASC) device employing (Ni0.33 Co0.67 )Se2 CHSs as positive electrode and activated carbon (AC) as negative electrode is also fabricated, which displays a high energy density of 29.1 Wh kg −1 at a power density of 800 W kg −1 . These electrochemical results indicate the hierarchical (Ni0.33 Co0.67 )Se2 CHSs could be promising electrode materials for pseudocapacitors. The present work might also contribute to the rational construction of metal selenides with complex hollow structures for high-performance energy storage. Graphical abstract: Hierarchical (Ni0.33 Co0.67 )Se2 complex hollow spheres were synthesized, which exhibited excellent electrochemical performance as electrode materials for pseudocapacitors. Image 1 Highlights: Hierarchical (Ni0.33 Co0.67 )Se2 complex hollow spheres (CHSs) were synthesized via a simple method. The hierarchical (Ni0.33 Co0.67 )Se2 CHSs exhibited excellent electrochemical performance for pseudocapacitors. An asymmetric supercapacitor based on the (Ni0.33 Co0.67 )Se2 CHSs as positive electrode was also fabricated.